2021
DOI: 10.3390/children8100874
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Use of Regulatory Talk with Toddlers in Chile and the US: How Do Cultural Values and Children’s Gender Affect Mothers’ Regulatory Talk at 12 and 30 Months?

Abstract: Studies have shown that Chilean and US infants differ in their levels of self-regulation. One of the mechanisms of early socializing is the use of language, particularly mental state language. The current study seeks to deepen our knowledge of the ways in which mental state language is related to socialization processes in early childhood, including the ways both culture and children’s gender influence a mothers’ use of mental state talk. We used a quantitative and descriptive approach with 109 mothers and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…A study by Torres (2017) found that while Chilean primary school children showed similar levels of behavior regulation compared to British children, psychological factors contributing to the expression of behavior regulation differed. Further, Santelices et al (2021) suggested that lower levels of behavior regulation in Chilean children compared to US-American children might be related to a higher culture-specific acceptance of external regulation in Chilean children. In Germany, a European industrial country, an independent self-construal is prominent, and a strong focus is put on enhancing individual responsibility, independence, and autonomous behavior regulation (Keller and Lamm, 2005).…”
Section: Cross-cultural Aspects Of Behavior Regulationmentioning
confidence: 99%
“…A study by Torres (2017) found that while Chilean primary school children showed similar levels of behavior regulation compared to British children, psychological factors contributing to the expression of behavior regulation differed. Further, Santelices et al (2021) suggested that lower levels of behavior regulation in Chilean children compared to US-American children might be related to a higher culture-specific acceptance of external regulation in Chilean children. In Germany, a European industrial country, an independent self-construal is prominent, and a strong focus is put on enhancing individual responsibility, independence, and autonomous behavior regulation (Keller and Lamm, 2005).…”
Section: Cross-cultural Aspects Of Behavior Regulationmentioning
confidence: 99%